Analysis of Law No. 13 of 2011 concerning Handling the Poor in Development and Distribution of Direct Cash Assistance Funds from Village Funds in Pematang Tengah Village, Tanjung Pura District, Langkat Regency, from the Perspective of Fiqh Siyasah Dusturiyah - Lubis, Rianda; Pasaribu, Ilhamsyah (LEGAL BRIEF, 2025)
The aim of this research is to find out what has been done in the village government's work plan programs, such as building houses and distributing direct cash assistance funds, whether these programs are in accordance with the law and siyasah fiqh or not. However, researchers found that the programs implemented by the Langkat district government were not in accordance with Law no. 13 of 2011, article 14. because in the village there are already houses that have been built but only a few, but for the rest the Langkat district social services government is targeting houses to be built because there are only a few houses that have not been built, therefore the district social services government has not yet directly carried out the order of Law no. 13 of 2011 article 14.